Education on Prevention of Bullying Behavior: Eradicating the Seeds of Bullying in Elementary School Students - Setyastuti, Yuanita; Fahrianoor, Fahrianoor; Kumalawati, Rosalina; Yuliarti, Astinana; Hidayat, Muhammad Nizar (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This program was implemented at SDN Belitung Utara 3 Banjarmasin to provide education on bullying behavior to students and teachers. The aim of the program was to improve understanding related to bullying, its types, its impact, and prevention strategies. The program was conducted in several stages: (1) pre-test to measure students' initial knowledge, (2) education through socialization covering the understanding of bullying and preventive actions, (3) post-test to evaluate students' improved understanding after the socialization, and (4) program sustainability through the installation of